Medicine as an Object of Sociological Investigation - Tytmonas, Alfredas (Problemos, 1975)
The author aims at revealing the sociological aspect of medicine. The latter includes two groups of problems: 1) the place and importance of medicine in social life, the structure of social phenomena of medicine, etc.; 2) the specificity of professional medical activity, interrelation of organization, professionalization and institutionalization in medicine, the value-normative system of medical activity, etc. The author argues against the conceptions that reduce the sociological problems of medicine to the problems of social hygiene or consider these as the general object of medicine of sociology. In the author’s view in investigating the social aspects of human health and disease, one deals with the medical point of view on social reality. The investigation of medicine as of a definite social phenomenon belongs to sociology.